2012
DOI: 10.1590/s0004-28032012000200004
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic esophagitis: manometric and pHmetric findings

Abstract: -Context -Eosinophilic esophagitis is an entity characterized by an esophageal inflammatory infiltrate of eosinophils, manifested by dysphagia, intermittent food impactions and symptoms similar to gastroesophageal reflux disease (GERD), that predominantly affects young adults. There may be association of eosinophilic esophagitis with GERD, and motor abnormalities have been described. Objective -The main objectives of this study are to describe the findings at esophageal manometry and pH monitoring in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Several studies have been published investigating esophageal dysmotility in patients with EoE. Many of these early investigations revealed variable motility patterns, but were significantly limited by the use of conventional manometry . High‐resolution manometry (HRM), a diagnostic tool that has its origins in convention manometry tracings, has become the investigative study of choice in the evaluation of esophageal motility disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published investigating esophageal dysmotility in patients with EoE. Many of these early investigations revealed variable motility patterns, but were significantly limited by the use of conventional manometry . High‐resolution manometry (HRM), a diagnostic tool that has its origins in convention manometry tracings, has become the investigative study of choice in the evaluation of esophageal motility disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal motility is evaluated using manometry . Conventional and high‐resolution manometric studies have demonstrated a variety of motility disorders, which were present in 0–90% of EoE patients . The observed motility patterns are not specific for EoE, and range from absent peristalsis to achalasia, diffuse esophageal spasm, nutcracker esophagus, panesophageal pressurization, and ineffective peristalsis (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, rather than exhibiting an increase in eosinophils, the smooth muscle of EoE patients presents an increase in mast cell numbers, with the TGF-b1 expressed by them possibly increasing the contractility of smooth muscle fibers [86], thereby modulating esophageal contractility. Hypertrophy of the muscularis mucosa along with the circular and longitudinal muscle layers has also been reported in patients with EoE [161], contributing to the esophageal dysfunction repeatedly demonstrated in pediatric [162] and adult EoE patients [163][164][165]. Finally, eosinophilic infiltration of the submucosal and myenteric neuronal plexus has also been documented in EoE [144].…”
Section: Cellular and Molecular Basis Of Tissue Remodeling In Eoementioning
confidence: 86%